Centrifuge-less deep eutectic solvent based magnetic nanofluid-linked air-agitated liquid–liquid microextraction coupled with electrothermal atomic absorption spectrometry for simultaneous determination of cadmium, lead, copper, and arsenic in food samples and non-alcoholic beverages. (30th May 2019) - Shirani, Mahboube; Habibollahi, Saeed; Akbari, Ali
Graphical abstract: Highlights: Centrifuge-less DES based magnetic nanofluid-linked air-agitated liquid–liquid microextraction. A new generation of green solvents as DESs based magnetic nanofluid was introduced. Toxic heavy metals of Cd, Pb, Cu, and As were analyzed in water, and food samples. High potential of CL-DES-MNF-AALLME for application in complex matrices. Abstract: In this research, the novel environmentally-friendly analytical method, Centrifuge-less deep eutectic solvent based magnetic nanofluid-linked air-agitated liquid–liquid microextraction (CL-DES-MNF-AALLME) coupled with ETAAS was proposed for simultaneous preconcentration of heavy metals of lead, arsenic, cadmium, and copper. In CL-DES-MNF-AALLME, the extraction solvent is novel magnetic nanofluid consists of DES based magnetic multiwall carbon nanotubes which can easily be separated from the media with no need to centrifugation. The detection limits of 4.2, 3, 3.5 and 3.6 ng L −1 were acquired for cadmium, lead, copper, and arsenic respectively. The proper closeness of enrichment factors in the range of 635–644.5 to preconcentration factor (640), confirm the quantitatively of the proposed extraction method with relative standard deviation of 2.5–3.1(%) (n = 7). The potential of the CL-DES-MNF-AALLME was considered in walnut, rice, tomato paste, spinach, orange juice, black tea, and water samples which showed high capability of the proposed method for application in the complex matrixes.